Family-Based Intervention Program for Parents of Substance-Abusing Youth and Adolescents. (5th October 2016) - Bisetto Pons, David; González Barrón, Remedios; Botella Guijarro, Álvaro
Abstract : The use of drugs among adolescents/youth often results in a high degree of distress for the family members who live with them. This in turn can lead to a deterioration of mental (psychological) health, hindering any attempt to successfully cope with the situation. The goal of our research was to study the effect of the Community Reinforcement and Family Training (CRAFT) program on parents of adolescents/young adult drug users. Study volunteers (n = 50 ) were parents from Valencia (Spain) that were divided into two groups. The experimental group (n = 25 ) was made up of parents whose sons and daughters exhibited problems with drug use and the constructed noncausal baseline group (n = 25 ) was made up of parents whose sons and daughters did not show any substance abuse problems. For both groups, self-esteem (Rosenberg Self-Esteem Scale), depression (BDI-II), anxiety (STAI), and anger (STAXI-II) were evaluated before and after the application of the CRAFT program. Results show a significant improvement in the experimental group's self-esteem, depression, and anger state and a decrease in negative moods. These changes in parents produce a positive effect on their substance-using sons and daughters: of the 25 participants, 15 contacted specialized addiction treatment resources for the first time.